2006
DOI: 10.1002/macp.200600372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Curing of Liquid‐Crystalline Epoxy Resins Containing a Biphenyl Mesogen

Abstract: Summary: Liquid crystalline epoxies with a biphenyl mesogenic group have been widely studied although it is still in contention as to whether the diglycidyl ether of DGEBP shows a thermotropic phase. DEPBP was synthesized by partial oxidation and the liquid crystalline properties were investigated. Despite their similar structures their molecular weights are quite different. DEPBP has a distinct molecular weight, while DGEBP shows a molecular weight distribution. DEPEBP was also synthesized and characterized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…27,28 They are highly promising polymeric materials as the oriented liquid crystal networks can be used as an optical compensation film for a liquid crystal display. 29 Fabrication of uniaxially oriented nematic networks from diepoxy monomer in presence of photointiator was demonstrated by Broer et al 30 A large number of reports are available on synthesis of liquid crystalline epoxy polymers with variety of nonphotoactive mesogens [31][32][33][34][35] and photoactive mesogens [36][37][38][39][40] due to their potential utilization in the development of magnetic/ electric field or light induced liquid crystalline networks formation.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 They are highly promising polymeric materials as the oriented liquid crystal networks can be used as an optical compensation film for a liquid crystal display. 29 Fabrication of uniaxially oriented nematic networks from diepoxy monomer in presence of photointiator was demonstrated by Broer et al 30 A large number of reports are available on synthesis of liquid crystalline epoxy polymers with variety of nonphotoactive mesogens [31][32][33][34][35] and photoactive mesogens [36][37][38][39][40] due to their potential utilization in the development of magnetic/ electric field or light induced liquid crystalline networks formation.…”
Section: Introductionmentioning
confidence: 99%
“…But the curing rate of MPEPEB with the diamine is found to be far higher than that of diglycidyl ether of bisphenol A (DGEBA), which seems to be attributed to the appearance of an LC phase in the literature. [39,44] The curing rates at different conversions of MPEPEB/ DAE in a temperature range from 80 to 140 8C obtained from isothermal DSC analysis are plotted in Figure 4. The curing reaction obeys n-th order kinetics as a whole, although an inconspicuous abnormal increase of the curing rate appears at the initial stage when the curing temperature is lower than 100 8C.…”
Section: Curing Of Mpepeb With Daementioning
confidence: 99%
“…[30,42] In a previous paper, it was found that the E a of the curing reaction of 4,4 0 -di(2,3-epoxypropyloxy)biphenyl (DEPBP) with DDM increased about 40 kJ Á mol À1 . [44] All this indicates that the increase of A, which in turn indicates an increase of collision frequency, and the increase of E a in the curing of MPEPEB/DAE may be attributed to the appearance of a mesogenic phase. [2] It is also noted that the E a obtained by the dynamic method is much higher than that by the isothermal study.…”
Section: Curing Of Mpepeb With Daementioning
confidence: 99%
“…However, they also have low fracture toughness, and the incorporation of liquid crystalline structure is one of effectual way to make a modification. So recently, many studies have been focused on the subject of liquid crystalline thermosets due to their prior properties compared with ordinary epoxy resins, but most of these reports give the emphasis on the studies of liquid crystalline epoxy resins (LCERs) [4][5][6][7][8][9][10]. Well, as is known that curing agents can influence the structure of the networks, and the formation of LC phase in the networks can also be affected (even be determined) by the structure of the curing agents to crosslink the epoxy monomers.…”
Section: Introductionmentioning
confidence: 99%